A Descriptive Study on Common Causes, Treatment and Outcome of Neck Injuries - Hamna Abdu Nazir; Wilson Desai; Reshma Chavan; Sarvesh Azgaonkar (Bengal Journal of Otolaryngology and Head Neck Surgery, 2024)
Introduction: ENT experts manage neck traumas, particularly penetration neck injuries or cut throat injuries, which violate the platysma muscle layer. The aim of this study was to assess further in detail about the sociodemographic status, etiology, presentation of patients, treatment provided and its outcome. Material and Methods: This study was carried out in the Department of ENT at a tertiary care hospital from January 2020 to January 2023. The study is retrospective. Total 17 cases of cut throat injuries, irrespective of age and sex, were included in the study. Patients with insignificant injuries to neck and those with multiple traumas to other body parts were excluded from this study. Results: Among the 17 patients included in the study, most of them were males and belonged to upper lower socioeconomic class according to modified Kuppuswamy scale. The most common mode of neck injury was by suicide and four of them were suffering from depression. The most common site involved was the zone II. Conclusions: Poor socioeconomic status and unemployment negatively impact mental health, leading to homicidal injuries. Resolving societal issues like poverty and drug addiction, implementing government enforcement measures, and improving communication systems can reduce complications and death rates.